Wound Healing and Antioxidant Properties of Eucheuma Cottonii Extract on Sprague Dawley Rats - Fard, Samaneh Ghasemi (2009)
Wounds and their treatment are a big burden on the healthcare system, both in terms of cost, time and energy of care required. The lost in productivity and decreased quality of life is immeasurable. This study reports on the potential wound healing and antioxidant properties of oral consumption of ethanolic and aqueous extracts of Eucheuma cottonii. Two cm diameter excision of skin wound model was used, with honey (100 mg/kg body weight) as positive control and untreated normal rats as negative control groups. Both extracts significantly (P<0.05) increased the rate of wound contraction, better than honey. The extracts decreased lipid peroxidation in the plasma and increased erythrocyte antioxidant enzyme activities (superoxide dismutase) and reduced glutathione compared to both the positive and negative control groups. The ethanolic extract was more effective than the aqueous extract by 20%. Histopathological wound tissue observations showed both extracts significantly